Reading Spencer and Gillen - Morphy, Howard (Sophia, 2012)
In this paper I provide an interpretative reading Spencer and Gillen. What is read depends in part on what one is looking for, on the purposes for which it is being read, and, what is there to be read depends partly on the audiences that the author has in. I provide a critique of social Darwinist and post-colonial readings of their work. I employ the concept of a motivating theme, which can be applied to segments of the text, which share a common purpose. The themes reflect the ways in which different scholars — historians and anthropologists — have read into the text. I will consider three categories of motivating themes: general contextualisations, ethnographic descriptions, and explanations of data. My discussion of their explanatory approach is centred on their analysis of ritual performances. The accounts of the rituals are not just unanalysed ethnography but are ordered by relating ritual event to social organisation. The centrality of ritual to Aboriginal society has contributed to the lasting impact of their work.